Parental engagement and early interactions with preterm infants during the stay in the neonatal intensive care unit: protocol of a mixed-method and longitudinal study. Issue 2 (2nd February 2017) - Stefana, Alberto; Lavelli, Manuela
Abstract : Introduction: The preterm infants' developmental outcomes depend on biological and environmental risk factors. The environmental factors include prolonged parental separation, less exposure to early mother/father–infant interactions and the parents' ability to respond to the trauma of premature birth. In the case of premature birth, the father's ability to take an active part in the care of the infant from the start is essential. The parents' emotional closeness to the preterm infant hospitalised in the neonatal intensive care unit (NICU) may be crucial to the well-being of the newborn, the development of mutual regulation, the establishment of a functioning parent–infant affective relationship and the parents' confidence in their ability to provide care for their baby. Methods and analysis: This is a mixed-method, observational and longitudinal study. The methodological strategy will include: (1) ethnographic observation in a level III NICU located in Italy for a duration of 18 months; (2) 3-minute video recordings of mother–infant and father–infant interaction in the NICU; (3) a semistructured interview with fathers during the infants' hospital stay; (4) 3-minute video recordings of mother–infant and father–infant face-to-face interaction in the laboratory at 4 months of corrected age; (5) self-report questionnaires for parents on depression and quality of the couple relationship at the approximate times of the video recording sessions. Ethics and dissemination: The study protocol was approved by the Ethical Committee for Clinical Trials of the Verona and Rovigo Provinces. Results aim to be published in international peer-reviewed journals, and presented at relevant national and international conferences. This research project will develop research relevant to (1) the quality and modalities of maternal and paternal communication with the preterm infant in the NICU; (2) the influence of maternal/paternal social stimulation on the infant behavioural states; (3) the quality and modalities of paternal support to the partner and possible influences on mother–infant relationship.